Evaluation of Potential Reservoir Deficiency Due to Climate Change, Kesem Kebena Dam, Ethiopia - Shumie, Melese Chanie (Journal of Environmental Geography, 2019)
Flood is an excess inundation of water on a surface and difficult to manage. The flood occurred in previous decades of Afar region of Ethiopia, consequently, leads to the death of human beings, destruction of infrastructures, an annihilation of massive hydraulic structures, and downstream properties. The main responsible factors for the flood incidences of the region are climate change, global warming, deforestation, and desertification. Climate change, however, is the foremost reason of increasing flood hazard. To coincide with this, hydraulic structures are designed based on the previously recorded flow data of a river. In Ethiopia, numerous earthen dams are constructed. The water storage capacity of dams is determined by the appraised flood of the upstream catchment: however, when the catchment flood increases due to climate extremes, the constructed structures cannot carry and going to demolish. The extra water that rises due to climate change from the catchment has to be removed before joins to the reservoir. This study has evaluated the potential reservoir deficiency of Kesem Kebena dam due to climate change. The study has comprehended different methods based on scientific criteria and selects the appropriate measure. As per the research output, the excess water that will arise from the catchment and add to the reservoir can be controlled by diversion floodways (Emergency spillways). The study has determined the amount of excess flood join to the reservoir for the excess rainfall incident month (August) for 100 years return period. Its magnitude is 85.76m3/s. The emergency spillway is the best means to divert such unwanted water before joining to the reservoir. Its hydraulic design is discussed in the study.